2015
DOI: 10.1016/j.msea.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Measuring residual stress and its influence on properties of porous ZrO2/(ZrO2+Ni) ceramics

Abstract: Ceramic-metal functionally graded materials (FGMs) have been extensively used in aerospace engineering where high strength and excellent heat insulation materials are desired. However, their performance depends highly on the internal residual stress, which is generated inevitably due to the thermal mismatch of ceramic and metal. In this paper, based on the nanoindentation test, the field distribution of the residual stress of porous ZrO2/(ZrO2+Ni) ceramic-metal FGMs is measured. The residual stress field measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…A large number of researchers have turned their attention to FGMs. Some of them focused on the analysis of the production process of these materials as well as on the modelling and simulation of the process [2][3][4][5][6] while others turned their attention to the inevitably generated residual stresses of FGMs due to thermal mismatch of each basic material using experimental and analytical methods [7,8] or their characterization [1]. Over time, a number of techniques have been developed in order to obtain FGMs: Powder metallurgy, vapor deposition, solid free form fabrication, centrifugal casting, and additive manufacturing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of researchers have turned their attention to FGMs. Some of them focused on the analysis of the production process of these materials as well as on the modelling and simulation of the process [2][3][4][5][6] while others turned their attention to the inevitably generated residual stresses of FGMs due to thermal mismatch of each basic material using experimental and analytical methods [7,8] or their characterization [1]. Over time, a number of techniques have been developed in order to obtain FGMs: Powder metallurgy, vapor deposition, solid free form fabrication, centrifugal casting, and additive manufacturing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Microstructures and properties of the porous ZrO 2 /(ZrO 2 þ Ni) sandwich ceramics were experimentally studied in our previous work [11][12]. Then a finite element model is established to verify the correctness of the analytical model.…”
Section: Introductionmentioning
confidence: 99%
“…The most potential dangerous locations of the bolted joint are the interface between the bearing load layer (ZrO 2 þ 30 vol.%Ni) and the transition layer (ZrO 2 þ 15 vol.%Ni), and the root of the first thread, which are shown in Fig. 5a and are marked as locations B and C. This is because the residual thermal stress at location B is the maximum tensile stress, which can be seen in our previous work [22]. Besides, stress concentration is the most severe at location C. In the present work, we only give results of three representative situations, namely, Little preload (15 MPa), Critical preload (33.5 MPa) and Big preload (50 MPa).…”
Section: Transient Thermodynamic Behaviormentioning
confidence: 76%
“…For example, the ceramicemetal FGMs can be designed to take advantages of the mechanical strength of metals and the heat and corrosion resistance of ceramics [19,20]. In our previous work, we fabricated and experimentally investigated the microstructure and thermomechanical properties of the porous ZrO 2 /(ZrO 2 þ Ni) ceramics and found that they had a low thermal conductivity and high strength [21,22]. Therefore, the ceramicemetal FGMs can be a potential candidate for heat shorts blocking joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation